DEVELOPING A MULTIMEDIA POWERPOINT PRESENTATION ON THE HUMAN CIRCULATORY SYSTEM FOR JUNIOR HIGH SCHOOL STUDENTS IN PAPUA - Ibnu Rusid; I Nyoman Sudana Degeng; Nurmida Catherine Sitompul (LPPM Universitas PGRI Semarang, 2024)
A biology curriculum consists of several topics that should be taught using appropriate media based on the type of information. The use of Multimedia PowerPoint is chosen because it is accessible without the need for an internet connection, making it a suitable solution for schools in Papua that lack infrastructure. This research aims to develop a Multimedia PowerPoint presentation on the Human Circulatory System for Junior High School students in Papua, with the goal of enhancing students' understanding of biology. The research method used is Research and Development, following the procedure outlined in the Borg & Gall Model. The developed product was reviewed by several experts and deemed viable. Subsequent assessment by students a yielded positive result. Questionnaires were used for assessment, and data analysis was conducted using percentages. The results of the development of the Multimedia PowerPoint on the Human Circulatory System are as follows: (1) The average assessment from material/content experts is 93%. (2) The average assessment from media experts is 100%. (3) The average assessment from design experts is 89%. (4) The average assessment from individual trials is 88%. (5) The average assessment from small group trials, is 90%. (6) The average assessment from large group trials is 91%. In conclusion, the Multimedia PowerPoint is a feasible instructional media for teaching the Human Circulatory System to Junior High School students, particularly in the Papua region.